2023
DOI: 10.3389/fcvm.2022.1053765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of e-health intervention on disease management in patients with chronic heart failure: A meta-analysis

Abstract: ObjectiveThe aim of this meta-analysis was to assess the impact of e-health interventions on disease management in patients with CHF.MethodsSix databases including Embase, Web of Science, Scopus, PubMed, Cochrane, and EBSCO were searched by computer. The search time is before May 1, 2022. Odds ratios (OR) were used for binary categorical data and weighted mean differences (WMD) for continuous variables. The 95% confidence intervals (CI) were used to express the effect sizes for both count and measurement data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“… 26 The combination of chronic disease self-management and the 5G internet has become unavoidable. 27 However, old people with chronic NCDs still lack the opportunity and ability to get health information from the internet 28 and are unable to make good use of smart health devices to manage diseases. 29 A systematic review indicated low e-health literacy of old Chinese, and it can be affected by a number of influencing factors at the individual, interpersonal, and social/community levels.…”
Section: Introductionmentioning
confidence: 99%
“… 26 The combination of chronic disease self-management and the 5G internet has become unavoidable. 27 However, old people with chronic NCDs still lack the opportunity and ability to get health information from the internet 28 and are unable to make good use of smart health devices to manage diseases. 29 A systematic review indicated low e-health literacy of old Chinese, and it can be affected by a number of influencing factors at the individual, interpersonal, and social/community levels.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, eHealth can also deliver personalised and timely coaching to patients (and their families) with the goal of promoting engagement with self-care maintenance, or communication with care providers to inform self-care management. In the case of CVD, systematic reviews of evidence have shown that eHealth interventions can have a positive impact on the patients' (digital) health literacy (Verweel et al, 2023), their adherence to a healthy diet (Thom et al, 2023) and physical activity (Patel et al, 2023), and on important health outcomes such as reduced mortality, hospitalization, and quality of life (Ding et al, 2023). Adding to this, qualitative studies have also noted how patients recognise and value the perceived benefits of technology-based interventions (Sivakumar et al, 2023).…”
Section: The Promise Of Ehealth For Self-care Supportmentioning
confidence: 99%